Orientalism as a stylistic direction in the art of the West (Journal of Philosophy Culture and Political Science, 2016)
In this article the term of orientalism, and its influence on culture of the West is considered, in particular characteristics of influence of the East on art of architecture, an interior and furniture are analysed . It is revealed that the Orientalism plays in the society of the West an ambiguous role – deep expansion of a psychological state, release from the existing restrictions imposed by the industry and in each of them the appeal to other cultural tradition repeats. Result of interaction of the East and West are attempts of revival of the European craft in general, or to develop creative thinking, proceeding from that that East culture was perceived not only as “ alien “or “other”, but also as creative inspiration for the West.
Keywords: Orientalism; culture; east; art; interior; craft.